2013
DOI: 10.1002/pst.1595
|View full text |Cite
|
Sign up to set email alerts
|

The current state of Bayesian methods in medical product development: survey results and recommendations from the DIA Bayesian Scientific Working Group

Abstract: Bayesian applications in medical product development have recently gained popularity. Despite many advances in Bayesian methodology and computations, increase in application across the various areas of medical product development has been modest. The DIA Bayesian Scientific Working Group (BSWG), which includes representatives from industry, regulatory agencies, and academia, has adopted the vision to ensure Bayesian methods are well understood, accepted more broadly, and appropriately utilized to improve decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…A survey carried out by the Drug Information Association (DIA) Bayesian Scientific Working Group of industry statisticians in 2012 identified "a lack of clarity of the regulatory position and/or lack of guidance" as one of the 4 main barriers to the implementation of Bayesian methodology. 7 Guideline expresses a major concern about only using historical controls (ie, the inability to control bias), but also describes the usefulness of such controls under certain scenarios. Guideline describes situations where appropriately and carefully chosen historical controls are more persuasive and potentially less biased.…”
Section: Principles For the Use Of Historical Controls In A New Clinimentioning
confidence: 99%
See 1 more Smart Citation
“…A survey carried out by the Drug Information Association (DIA) Bayesian Scientific Working Group of industry statisticians in 2012 identified "a lack of clarity of the regulatory position and/or lack of guidance" as one of the 4 main barriers to the implementation of Bayesian methodology. 7 Guideline expresses a major concern about only using historical controls (ie, the inability to control bias), but also describes the usefulness of such controls under certain scenarios. Guideline describes situations where appropriately and carefully chosen historical controls are more persuasive and potentially less biased.…”
Section: Principles For the Use Of Historical Controls In A New Clinimentioning
confidence: 99%
“…A survey carried out by the Drug Information Association (DIA) Bayesian Scientific Working Group of industry statisticians in 2012 identified “a lack of clarity of the regulatory position and/or lack of guidance” as one of the 4 main barriers to the implementation of Bayesian methodology. 7 In 2016, representatives from FDA’s Centers for Drug Evaluation and Research (CDER), Biologic Evaluation and Research (CBER), and Devices and Radiological Health (CDRH) participated in a workshop “Substantial Evidence in 21st Century Regulatory Science: Borrowing Strength from Accumulating Data” that focused on methods to incorporate historical information. 8 This indicates a growing acceptance by regulators of using historical controls for late-stage drug development.…”
Section: Principles For the Use Of Historical Controls In A New Clinimentioning
confidence: 99%
“…This result supports findings of the DIA Bayesian Scientific Working Group (BSWG), which reported that there are more opportunities for statisticians to implement Bayesian adaptive design approaches in early phase than in late phase clinical development. 27 In very general terms, the chief advantages of Bayesian approaches are the ability to easily incorporate external information into an analysis and mathematical flexibility in fitting certain complicated models that may be intractable in a classical framework. The fact that CBER primarily receives Bayesian proposals for dose-finding models in early-phase trials suggests that it is the latter rather than the former factor spurring Bayesian applications in regulatory submissions to CBER.…”
Section: Lessons From Our Review Experiencesmentioning
confidence: 99%
“…A special issue on Bayesian Statistics was published in 2014 with coverage of a variety of areas, including network meta‐analysis in drug safety . The issue also contained a paper by the DIA Bayesian Scientific Working Group reporting a survey showing that “having access to fully worked case examples was considered the most helpful factor to start applying Bayesian approaches.” In recent years, we have encouraged Andy Grieve to share his knowledge and experience with case studies which are easy to follow and can hopefully cast light on a variety of areas of work which can be improved by a Bayesian approach …”
Section: Regulatory and Professional Applicationmentioning
confidence: 99%